Shackleton : Antarctic odyssey - Bertozzi, Nick (2014)
Presents, in graphic novel format, the adventures of explorer Ernest Shackleton in the Antarctic.
Keywords: Shackleton, Ernest Henry, -- Sir, -- 1874-1922 -- Comic books, strips, etc; Shackleton, Ernest Henry, -- Sir, -- 1874-1922 -- Juvenile literature; Explorers -- Great Britain -- Biography -- Comic books, strips, etc; Explorers -- Great Britain -- Biography -- Juvenile literature; Graphic novels; Antarctica -- Discovery and exploration -- British -- Comic books, strips, etc; Antarctica -- Discovery and exploration -- British -- Juvenile literature